Parameter Optimisation of a H-type Three-blade Contra-rotating Vertical-axis Wind Turbine at Low Tip-speed Ratio - Z. Zhao; K. Chen; Q. Wang; T. Su; H. Hu (Journal of Applied Fluid Mechanics)
Renewable energy sources such as wind energy can alleviate climate deterioration and the global energy crisis, and a major piece of equipment for capturing wind energy is the vertical-axis wind turbine (VAWT), with contra-rotating VAWTs (CR-VAWTs) having received focused attention because of their excellent stability. In the study reported here, Taguchi’s method and computational fluid dynamics were used to optimise the four main parameters in the configuration of a three-blade H-type CR-VAWT, i.e. rotor spacing (S), diameter-to-height ratio (D/H), phase angle (α), and rotational direction (r). The optimum CR-VAWT was derived, and its power coefficients were compared with those of a stand-alone VAWT under low tip-speed ratio (TSR). It was found that D/H has the most effect (81.21%) on the CR-VAWT power performance, followed by α (7.37%) and then r (5.83%), with S having the least effect (5.59%). Compared to the stand-alone VAWT, the average power coefficient of the optimum CR-VAWT is much smaller when the TSR is less than 1.25, but the power performance of the latter gradually prevails as the TSR increases. At a TSR of 1.6, the optimum CR-VAWT has an average power factor improvement of 10.6% over the stand-alone VAWT. At the same time, the maximum total torque of the optimum CR-VAWT is only 6% of that of the stand-alone VAWT, giving the CR-VAWT good stability.